Economical analyses of build-operate-transfer model in establishing alternative power plants - Yumurtaci, Zehra; Erdem, Hasan Huseyin (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
The most widely employed method to meet the increasing electricity demand is building new power plants. The most important issue in building new power plants is to find financial funds. Various models are employed, especially in developing countries, in order to overcome this problem and to find a financial source. One of these models is the build-operate-transfer (BOT) model. In this model, the investor raises all the funds for mandatory expenses and provides financing, builds the plant and, after a certain plant operation period, transfers the plant to the national power organization. In this model, the object is to decrease the burden of power plants on the state budget. The most important issue in the BOT model is the dependence of the unit electricity cost on the transfer period. In this study, the model giving the unit electricity cost depending on the transfer of the plants established according to the BOT model, has been discussed. Unit electricity investment cost and unit electricity cost in relation to transfer period for plant types have been determined. Furthermore, unit electricity cost change depending on load factor, which is one of the parameters affecting annual electricity production, has been determined, and the results have been analyzed. This method can be employed for comparing the production costs of different plants that are planned to be established according to the BOT model, or it can be employed to determine the appropriateness of the BOT model. (c) 2006 Published by Elsevier Ltd.
Keywords: build-operate-transfer model; economical analysis; power plants; RISKS; Thermodynamics; Energy & Fuels; Mechanics